Biotic and environmental dynamics through the Late Jurassic–Early Cretaceous transition: evidence for protracted faunal and ecological turnover. (17th February 2016) - Tennant, Jonathan P.; Mannion, Philip D.; Upchurch, Paul; Sutton, Mark D.; Price, Gregory D.
ABSTRACT: The Late Jurassic to Early Cretaceous interval represents a time of environmental upheaval and cataclysmic events, combined with disruptions to terrestrial and marine ecosystems. Historically, the Jurassic/Cretaceous (J/K) boundary was classified as one of eight mass extinctions. However, more recent research has largely overturned this view, revealing a much more complex pattern of biotic and abiotic dynamics than has previously been appreciated. Here, we present a synthesis of our current knowledge of Late Jurassic–Early Cretaceous events, focusing particularly on events closest to the J/K boundary. We find evidence for a combination of short‐term catastrophic events, large‐scale tectonic processes and environmental perturbations, and major clade interactions that led to a seemingly dramatic faunal and ecological turnover in both the marine and terrestrial realms. This is coupled with a great reduction in global biodiversity which might in part be explained by poor sampling. Very few groups appear to have been entirely resilient to this J/K boundary 'event', which hints at a 'cascade model' of ecosystem changes driving faunal dynamics. Within terrestrial ecosystems, larger, more‐specialised organisms, such as saurischian dinosaurs, appear to have suffered the most. Medium‐sized tetanuran theropods declined, and were replaced by larger‐bodied groups, and basal eusauropods were replaced by neosauropod faunas. The ascent of paravian theropods is emphasised by escalated competition with contemporary pterosaur groups, culminating in the explosive radiation of birds, although the timing of this is obfuscated by biases in sampling. Smaller, more ecologically diverse terrestrial non‐archosaurs, such as lissamphibians and mammaliaforms, were comparatively resilient to extinctions, instead documenting the origination of many extant groups around the J/K boundary. In the marine realm, extinctions were focused on low‐latitude, shallow marine shelf‐dwelling faunas, corresponding to a significant eustatic sea‐level fall in the latest Jurassic. More mobile and ecologically plastic marine groups, such as ichthyosaurs, survived the boundary relatively unscathed. High rates of extinction and turnover in other macropredaceous marine groups, including plesiosaurs, are accompanied by the origin of most major lineages of extant sharks. Groups which occupied both marine and terrestrial ecosystems, including crocodylomorphs, document a selective extinction in shallow marine forms, whereas turtles appear to have diversified. These patterns suggest that different extinction selectivity and ecological processes were operating between marine and terrestrial ecosystems, which were ultimately important in determining the fates of many key groups, as well as the origins of many major extant lineages. We identify a series of potential abiotic candidates for driving these patterns, including multiple bolide impacts, several episodes of flood basalt eruptions, dramatic climate change, and major disruptions to oceanic systems. The J/K transition therefore, although not a mass extinction, represents an important transitional period in the co‐evolutionary history of life on Earth.